Di-(2-ethylhexyl)phthalate and Pyranon Derivated from Endophytic fungi Penicillium sp the Leave of Kunyit Putih (Curcuma zedoaria) - Muharni Muharni; Fitrya Fitrya; Milanti Okta Ruliza; Dwi Anjar Susanti; Elfita Elfita (Universitas Gadjah Mada, 2014)
Two compounds from cultivation of the endophytic fungi Penicillium sp of leaves of kunyit putih (Curcuma zedoaria have been isolated. The endophytic fungus was cultivated on 5 L of Potatos Dextrose Broth (PDB) medium at room temperature (no shaking) for 3 weeks. The cultures were extracted with ethyl acetate to afford 3.0 g of residue after removal of the solvent under reduced pressure. The extract was separated and purified by silica gel column chromatography (CC) and afforded two pure compounds as colorless oily liquid (compound 1) and yellow crystal (compound 2). The structure of these compounds were characterized by detailed UV, IR, and NMR spectroscopic analysis and compound 1 as well as comparison with the reported data. Base on spectra analysis the compound 1 was determined as Di-(2-ethylhexyl)phthalate and compound 2 as 5-(4’-ethoxy-2’-hydroxy-5’-methyl-2’,3’-dihydrofuran-3’-il (hydroxy) methyl-4-isopropyl-3-methyl-2-pyran-2-on). Compound 1 is not new compound, but it is new for endophytic fungus from C. zeodoria and compound 2 is new compound.